2022
DOI: 10.3389/fonc.2022.852095
|View full text |Cite
|
Sign up to set email alerts
|

FNDC5 Causes Resistance to Sorafenib by Activating the PI3K/Akt/Nrf2 Pathway in Hepatocellular Carcinoma Cells

Abstract: In this study, we aimed to reveal the resistance mechanism of hepatocellular carcinoma (HCC) cells to sorafenib by exploring the effect of FNDC5 on sorafenib-induced ferroptosis in HCC cells. We compared the expression level of FNDC5 between sorafenib-resistant and sorafenib-sensitive HCC cell lines and the level of ferroptosis between the groups after treatment with sorafenib. We knocked down FNDC5 in drug-resistant cell lines and overexpressed it in sorafenib-sensitive HCC cell lines to further demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Although the KEAP1 was suppressed in both cell lines after combination treatment, the opposite effect was observed on NRF2 expression. Activation of the p62-Keap1-NRF2 pathway has been shown to protect HCC cells against ferroptosis [ 65 ], leading to the development of sorafenib resistance [ 66 ]. Orlistat alone caused reductions in xCT and GPX4, indicating that orlistat might be a potential ferroptosis inducer.…”
Section: Discussionmentioning
confidence: 99%
“…Although the KEAP1 was suppressed in both cell lines after combination treatment, the opposite effect was observed on NRF2 expression. Activation of the p62-Keap1-NRF2 pathway has been shown to protect HCC cells against ferroptosis [ 65 ], leading to the development of sorafenib resistance [ 66 ]. Orlistat alone caused reductions in xCT and GPX4, indicating that orlistat might be a potential ferroptosis inducer.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib is a small molecule multi-kinase inhibitor with multiple antitumor effects and is the first-line targeted drug for the treatment of HCC in the advanced stage (113). Numerous studies have shown that the inactivation of Ras/Raf/ERK pathway and the activation of PI3K/Akt/mTOR pathway plays a crucial role in sorafenib resistance (114)(115)(116)(117). CTCs are released from tumor tissue to the bloodstream and carry drug resistance information of the primary tumor or metastases, therefore pERK/pAkt phenotype of CTCs can be used to monitor the therapeutic effect and drug resistance of sorafenib (48).…”
Section: Drug Therapy Monitoringmentioning
confidence: 99%
“…Immunohistochemistry methods were used as our team did in previous experiments (31,32). Tumor samples from 60 individuals with liver cancer were obtained and xed in 4.0% paraformaldehyde before being embedded in para n. Next, the tissue wax blocks were sliced into 4-mm slices and treated with 3.0% hydrogen peroxide before being sealed with 5.0% FBS.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…A western blotting analysis was performed by our team as in the previous experiments (31,32). The total proteins were recovered from HCC cells by lysis with radioimmunoprecipitation assay buffer in a 4°C environment.…”
Section: Western Blottingmentioning
confidence: 99%